In griechischem oder orientalischem Geist? Moses Mendelssohn im Religionsdiskurs der Aufklärungszeit = In Greek or Oriental Spirit? Moses Mendelssohn in the Religious Discourses of the Enlightenment Period - Wittler, Kathrin (Aschkenas, 2022)
While Moses Mendelssohn’s reputation as a modern Socrates is well-known to scholars of eighteenth-century intellectual history, the opposite tendency to orientalise him has received less attention than it deserves. The paper discusses some examples, highlighting the interdependence of Greek and Oriental attributions. In their critical reactions to Mendelssohn’s Phädon (1767), a modern version of Socrates’ dialogues on the immortality of the soul, radical Pietist Johann Daniel Müller and Lutheran orthodox theologian Gottfried Joachim Wichmann sought to invalidate the Jewish Enlightener’s case for reason by orientalising him. At the end of the century, the religious tensions inherent in the uses of Greek and Oriental models for different Jewish and Christian denominational positions became visible in Johann Gottfried Schadow’s drawing Sokrates im Kerker (1800), a work commissioned by David Friedländer, whose Sendschreiben von einigen Hausvätern jüdischer Religion (1799) had just caused a stir with its bold statements in the spirit of Deism.